2022
DOI: 10.1021/acs.bioconjchem.2c00076
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Anticancer Activity of Triptycene–Peptide Hybrids that Induce Paraptotic Cell Death in Cancer Cells

Abstract: We report on the design and synthesis of triptycene–peptide hybrids (TPHs), 5, syn-6, and anti-6, which are conjugates of a triptycene core unit with two or three cationic KKKGG peptides (K: lysine and G: glycine) through a C8 alkyl chain. It was discovered that syn-6 and anti-6 induce paraptosis, a type of programmed cell death (PCD), in Jurkat cells (leukemia T-lymphocytes). Mechanistic studies indicate that these TPHs induce the transfer of Ca2+ from the endoplasmic reticulum (ER) to mitochondria, a loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Induction of paraptosis by cyclometalated iridium (Ir) complex-peptide hybrid (IPH) and CGP37157 (an inhibitor of a mitochondrial Na + /Ca 2+ exchanger) is also reported to be associated with membrane fusion between mitochondria and the ER, followed by Ca 2+ influx from the ER to mitochondria, and a decrease in the mitochondrial membrane potential ( ΔΨ m) ( Yokoi et al, 2022 ). It has been reported that paraptosis induced by iridium complex-peptide hybrids and triptycene-peptide hybrids are inhibited by carbonyl cyanide 3-chloroophenylhydrazone (CCCP), while paraptosis induced by a natural product such as celastrol is not inhibited by CCCP ( Yamaguchi et al, 2022 ; Yokoi et al, 2022 ).…”
Section: Recent Trends In Paraptosis Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of paraptosis by cyclometalated iridium (Ir) complex-peptide hybrid (IPH) and CGP37157 (an inhibitor of a mitochondrial Na + /Ca 2+ exchanger) is also reported to be associated with membrane fusion between mitochondria and the ER, followed by Ca 2+ influx from the ER to mitochondria, and a decrease in the mitochondrial membrane potential ( ΔΨ m) ( Yokoi et al, 2022 ). It has been reported that paraptosis induced by iridium complex-peptide hybrids and triptycene-peptide hybrids are inhibited by carbonyl cyanide 3-chloroophenylhydrazone (CCCP), while paraptosis induced by a natural product such as celastrol is not inhibited by CCCP ( Yamaguchi et al, 2022 ; Yokoi et al, 2022 ).…”
Section: Recent Trends In Paraptosis Researchmentioning
confidence: 99%
“…Paraptosis was induced in MCF-7 cells upon treatment with both diethyldithiocarbamate and B12b and if there is short exposure of DSFoxy along with this, it led to lysosomal cell death ( Solovieva et al, 2022 ). A triptycene-peptide hybrid: syn-6 and anti-6 is capable of inducing paraptosis in Jurkat cells by the loss of mitochondrial membrane potential and cytoplasmic vacuolation ( Yamaguchi et al, 2022 ). The membrane interaction between the poorly differentiated gastric adenocarcinoma, and tumour-associated tissue eosinophilia can result in the activation and degranulation of Eosinophil sombrero vesicles towards the tumour cells, which induced paraptosis in the tumour cells due to the formation of cytoplasmic vacuoles, and mitochondrial swelling ( Caruso et al, 2022 ).…”
Section: Recent Trends In Paraptosis Researchmentioning
confidence: 99%
“…Unrestrained proliferation is a hallmark of tumor cells, which evade growth inhibition by resisting cell death and evading immune-mediated killing. Induction of programmed cell death is an effective strategy in tumor therapy [20]. Studies have shown that programmed cell death has several modes, including apoptosis, neuroapoptosis, cell necrosis and ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that hybrid compounds of cyclometalated iridium­(III) (Ir­(III)) complexes with cyclic peptides that bind to death receptors (DRs) expressed on the cancer cells, which detect Jurkat cells and induce their apoptosis and necrosis-type cell death. , In addition, Ir­(III) complexes and triptycene compounds conjugated with cationic peptides such as KK­(K)­GG (K: lysine, G: glycine) sequences, which induce paraptosis, a non-apoptotic programmed cell death, in Jurkat cells and other cancer cell lines, were designed and synthesized. Therefore, our future efforts will be directed to the design and synthesis of hybrid compounds of poly­(bpy) ligands with DR-binding peptides and/or cationic peptide units, which would give the answers to the following question, which will be the dominant type of cell death, apoptosis and/or paraptosis, or other types.…”
Section: Discussionmentioning
confidence: 99%